Pemahaman Mendasar tentang Hakekat Ilmu dalam Tinjauan Filsafat: Ontologi, Epistemologi, dan Aksiologi - Pratiwi, Utari; Karneli, Yeni; Marsidin, Sufyarma (Siber Nusantara Publisher, 2024)
Knowledge is something that will never end throughout the span of life and there will always be updates along with the times. The development of this science cannot be separated from a person's way of thinking philosophically who is never satisfied with a result that has been found. So there will always be new discoveries to improve human knowledge. This research aims to examine in depth from a theoretical perspective the nature of science which includes ontology, epistemology and axiology. This type of research is library research where the data comes from various literature, books, notes, articles, journals and other references relevant to ontology, epistemology and axiology. Data is analyzed through the stages of collection, exploration, classification, processing and interpretation which are contained and described in descriptive form. The results of this research show that ontology is the main stage in giving birth to a science, namely discussing everything that exists which is identical to the question. Epistemolgy is the second stage which contains search activities to find answers to the object you want to research. Axiology focuses more on the usefulness of the results of the studies being researched. So it can be understood that ontology, epistemology and axiology are three aspects that cannot be separated and are interconnected in understanding a science.